2005
DOI: 10.1016/j.jaci.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pollen-mediated oxidative stress on immediate hypersensitivity reactions and late-phase inflammation in allergic conjunctivitis

Abstract: Our data suggest that ROS generated by NAD(P)H oxidases in pollen grains intensify immediate allergic reactions and recruitment of inflammatory cells in murine conjunctiva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 48 publications
3
91
1
2
Order By: Relevance
“…To confirm these data, we conducted DCF assays. 17 As shown in Fig 2, B and C, pollen grains exhibited bright DCF fluorescence. Interestingly, 72% to 81% of the freshly collected pollen grains showed intense fluorescence, whereas 35% (ragweed) and 40% (pigweed) of the pollen grains released SPPs (Fig 2, D).…”
Section: Oxidative Stress Augments Release Of Sppsmentioning
confidence: 62%
“…To confirm these data, we conducted DCF assays. 17 As shown in Fig 2, B and C, pollen grains exhibited bright DCF fluorescence. Interestingly, 72% to 81% of the freshly collected pollen grains showed intense fluorescence, whereas 35% (ragweed) and 40% (pigweed) of the pollen grains released SPPs (Fig 2, D).…”
Section: Oxidative Stress Augments Release Of Sppsmentioning
confidence: 62%
“…In addition, pollen itself contains an endogenous NADPH-oxidase activity, which functions to generate local signals in airway epithelium. These signals in turn trigger the early recruitment of granulocytes, contributing to allergic inflammation in the lung [36,37] and eye [38].…”
Section: Nox Enzymes and Asthmamentioning
confidence: 99%
“…Ragweed pollen-derived NADPH oxidase (8 -10) increases levels of reactive oxygen species in the epithelium and has critical roles in both sensitization to and the development of allergies in mouse models (8,9). Very recently, we have demonstrated that allergenic pollen grains showed NADPH oxidase activity that differed in intensity and localization according to the plant families and that the activity was mostly concentrated within insoluble fractions (11).…”
mentioning
confidence: 99%